The Role of Bhabinkamtibmas in Supporting Motor Vehicle Tax Arrears Collection During the Covid-19 Pandemic - Facha, Nyi Ayu Fitria; Sulchan, Achmad (Law Development Journal, 2021)
This study aims to analyze the role of Bhabinkamtibmas in supporting the collection of motor vehicle tax arrears during the covid-19 pandemic in the Demak police jurisdiction and the obstacles to implementing the role of Bhabinkamtibmas in supporting the collection of motor vehicle tax arrears during the covid-19 pandemic in the Demak police jurisdiction and the solutions. The approach method is sociological juridical; analytical descriptive research specifications; data sources are primary data and secondary data; data collection methods through field studies and literature studies; while the data analysis method used qualitative analysis. As an analytical tool, role theory, legal effectiveness theory and benefit theory are used. The results of the study show that the role of Bhabinkamtibmas in supporting the collection of motor vehicle tax arrears in the jurisdiction of the Demak police station is to submit a motor vehicle tax bill to motorized vehicle taxpayers. This role is effective in increasing the realization of PKB revenue in the Demak Regency. The obstacles to implementing the role of Bhabinkamtibmas in supporting the collection of motor vehicle tax arrears come from internal and external factors.